An analysis of co-movement in equity sector indices - Aminah Shari; Fauziah Mahat (Human Resource Management Academic Research Society (HRMARS), 2021)
This study examines the co-movement among equity sector returns of the Malaysian capital market. The relationship is investigated using Correlation-based on Ordinary Least Square (OLS) and Multivariate-GARCH Dynamic Conditional Correlation (DCC) to examines the volatilities and correlations of sectoral equity indexes. The study uses daily data that ranges from 5 February 1999 to 6 February 2019. The OLS result reveal that there is a strong co-movement between sectoral equity and the stock market prices except in tin and mining sector. While time-varying correlations among sectoral indexes are estimated using MGARCHDCC, the empirical results from this analysis show that the plantation, properties and tin and mining sectors have negative unconditional correlation with the stock market, which is a good sign of diversification advantages. The findings have important implications helping portfolio managers and investors to understand the co-movement of equity sectors and then formulate policy measures that encourage better portfolio diversification.